Intramural Needle Ablation for Refractory Premature Ventricular Contractions. (27th April 2022) - Dukkipati, Srinivas R.; Nakamura, Tomofumi; Nakajima, Ikutaro; Oates, Connor; Narui, Ryohsuke; Tanigawa, Shinichi; Sljapic, Tatjana; Whang, William; Koruth, Jacob S.; Choudry, Subbarao; Schaeffer, Benjamin; Fujii, Akira; et al.
Abstract : Background: Frequent premature ventricular contractions (PVCs) are often amenable to catheter ablation. However, a deep intramural focus may lead to failure due to inability of standard ablation techniques to penetrate the focus. We sought to assess the efficacy and safety of infusion needle ablation (INA) for PVCs that are refractory to standard radiofrequency ablation. Methods: Under 2 Food and Drug Administration approved protocols, INA was evaluated in patients with frequent PVCs that were refractory to standard ablation. Initial targets for ablation were selected by standard mapping techniques. INA was performed with a deflectable catheter equipped with an extendable/retractable needle at the tip that can be extended up to 12 mm into the myocardium and is capable of pacing and recording. After contrast injection for location assessment, radiofrequency ablation was performed with the needle tip using a temperature-controlled mode (maximum temperature 60 °C) with saline infusion from the needle. The primary end point was a decrease in PVC burden to <5000/24 hours at 6 months. The primary safety end point was incidence of procedure- or device-related serious adverse events. Results: At 4 centers, 35 patients (age 55.3±16.9 years, 74.2% male) underwent INA. The baseline median PVC burden was 25.4% (interquartile range, 18.4%–33.9%) and mean left ventricular ejection fraction was 37.7±12.3%. Delivering 10.3±8.0 INA lesions/patient (91% had adjunctive standard radiofrequency ablation also) resulted in acute PVC elimination in 71.4%. After a mean follow-up of 156±109 days, the primary efficacy end point was met in 73.3%. The median PVC burden decreased to 0.8% (interquartile range, 0.1%–6.0%; P <0.001). The primary safety end point occurred in 14.3% consisting of 1 (2.9%) heart block, 1 (2.9%) femoral artery dissection, and 3 (8.6%) pericardial effusions (all treated percutaneously). Conclusions: INA is effective for the elimination of frequent PVCs that are refractory to conventional ablation and is associated with an acceptable safety profile. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01791543 and NCT03204981.